The Impact of Academic Procartination on The Learning Achievement of Grade 11 Students at SMA X Bogor - Nadzifah Fiddiana; Intan Aulia; Durra Syahrina (Jurnal Syntax Transformation, 2024)
Procartination is behavior negative that is do procrastination in finish task academic so that influence results performance Study less students maximum. Research purposes This For describe about impact procartination academic student 11th grade at SMA X Bogor. Research methods use qualitative approach with method analysis descriptive with in-depth interview technique and non-participant observation. Research result found that procartination academic impact on low learning performance.